Contemplative Neuroscience and the Teaching of Writing: Mindfulness as Mental Training - Kate Chaterdon (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Updates in cognitive research show that even short-term exposure to contemplative and mindfulness teaching techniques may have the potential to train learners’ brains and enhance their ability to write.